Determine Effect of Carbothera Therapy on Foot and Leg Ulceration for Diabetic Patients in Endocrine and Diabetic Center at Al-Nasiriya City - Sameer Razak Oleiwi1, Oday Faris Washeel2, Hassan Al-Yassin3, Adel Gassab Mohammed4 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Diabetic foot is a serious complication of diabetes that aggravates the patient’s condition whilst also having significant socioeconomic impact. Increasing physicians ‘awareness and hence their ability to identify the «foot at risk,» along with proper foot care, may prevent diabetic foot ulceration and thus reduce the risk of amputation. Objectives: 1.Determine the socio demographic data on diabetic foot and leg ulceration 2.Determine the relationship of socio demographic data on diabetic foot and leg ulceration 3.Determine the Effeteness of Carbothera therapy upon diabetic foot and leg ulceration improvement Methodology: A descriptive study was conducted on a sample consisting of (50) patients is having diabetic foot and leg ulceration who were selected randomly from Endocrine and Diabetic Center in Nasiriya City. Diabetic patient who have diabetic foot and leg ulceration, carried out in Nasiriya city / endocrine and diabetic Center starting from January/ 2019 to July /2019 Results: 40% the age between 60-69 years ,males was 68%, the patients residing in the city (urban) by 66%,78% of them consider that their monthly income is not enough, infected with diabetes For diabetes for a period of 10 years and more is 76%, the average age of patients was 59 years, patients discovered diabetes disease was 66% , improvement in their health through the carbothera therapy 66% indicated a positive effect on the patients, a significant mean relationship at level of 8% between the urban and rural environment variable with improved carbothera therapy indicates that therapy is more effective when the patient has a more urban than rural. In addition, a very weak and statistically insignificant relationship between the patients is other demographic data and the improvement of carbothera therapy